2013
DOI: 10.1097/sla.0b013e31826c37f1
|View full text |Cite
|
Sign up to set email alerts
|

A Statewide, Community-Based Assessment of Alvimopan's Effect on Surgical Outcomes

Abstract: This study suggests that the actual utilization of alvimopan leads to a reduction in prolonged ileus and LOS in patients who underwent colectomy. By accelerating postoperative recovery, alvimopan has the potential to benefit patients and health care systems by improving outcomes, ensuring patient comfort, and reducing cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In total, 54 publications were included with a total number of 18 983 patients. Seventeen studies were RCTs , four were case–control studies , nine were prospective studies and 24 were retrospective studies . The methodological quality of the included studies is shown in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…In total, 54 publications were included with a total number of 18 983 patients. Seventeen studies were RCTs , four were case–control studies , nine were prospective studies and 24 were retrospective studies . The methodological quality of the included studies is shown in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…First, our dataset lacked colectomy-specific complications that may better explain extended LOS such as prolonged postoperative ileus, though the expected ileus rate for the cohort is far less than the amount of unexplained extended LOS. 23 Second, while our risk-adjustment models accounted for patient illness, procedure type and acuity, we lacked data on factors such as patient rurality, access to transportation, discharge planning and care coordination which undoubtedly influence LOS as well. Third, we analyzed a common gastrointestinal procedure and our results may not apply to different procedures.…”
Section: Discussionmentioning
confidence: 99%
“…(1113) While these studies consistently showed that alvimopan is associated with either faster return of bowel function or shorter LOS, the magnitude of effect varied between studies. While this variation is expected given differences between RCTs and non-randomized effectiveness evaluations, (21, 22) it complicates the determination of the effectiveness of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns over the effectiveness of alvimopan persist as several well-done observational studies have reported LOS savings greater than one day. (1113) Additionally, some believe that the cost of the drug is excessive and unwarranted even though it is estimated to be approximately $67.50 per pill or $937.50 for a full course of seven days of treatment (14) and few patients actually receive the full course. Both of these factors may prevent adoption of alvimopan in routine clinical care.…”
Section: Introductionmentioning
confidence: 99%